2019
DOI: 10.3846/jbem.2019.10160
|View full text |Cite
|
Sign up to set email alerts
|

Does Corruption Affects Business Innovation? Insights From Emerging Countries

Abstract: There are very different outcomes in the literature regarding the influences of corruption on business innovation and also arguments for both "sanding the wheels" and "greasing the wheels" approaches. The main goal pursued in this paper is to broaden the understanding of the corruption influence on business innovation, considering seven representative dimensions of corruption at governmental structures and institutions' level and also four relevant dimensions of business innovation, less approached so far. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Innovative firms have higher growth rates and are more profitable than non-innovators (Kalyar et al , 2020). Thus, higher corruption by bureaucrats to exploit these firms may hinder innovation (Awdeh and Hamadi, 2019; Pirtea et al , 2019; Xie et al , 2019; Ayyagari et al , 2014) [2]. On the other hand, if corruption allows firms to overcome red tape and other bureaucratic impediments, then such firms could innovate more (Panibratov and Michailova, 2019; Krammer and Jimenez, 2019; Krammer, 2019; Nyugen et al , 2016; Goedhuys et al , 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Innovative firms have higher growth rates and are more profitable than non-innovators (Kalyar et al , 2020). Thus, higher corruption by bureaucrats to exploit these firms may hinder innovation (Awdeh and Hamadi, 2019; Pirtea et al , 2019; Xie et al , 2019; Ayyagari et al , 2014) [2]. On the other hand, if corruption allows firms to overcome red tape and other bureaucratic impediments, then such firms could innovate more (Panibratov and Michailova, 2019; Krammer and Jimenez, 2019; Krammer, 2019; Nyugen et al , 2016; Goedhuys et al , 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the opinion of most of them, the very existence of corruption has seriously destroyed the development and innovation of economic entities. In an unstable environment, business innovation is a prerequisite for sustainable business improvement [2]. A survey of companies in 20 emerging countries found that the database results for the period 2006-2013 show that corruption has the most negative impact on business development and innovation, especially in emerging countries [3].…”
Section: The Impact Of Regional Corruption On Businessmentioning
confidence: 99%
“…Especially in some backward countries, proper bribery can lead to lower government requirements for business development, which can lead to a rapid rise in the region's economy and more opportunities for local businesses to do business. Officials who receive benefits have increased power over the progress of projects, so some people believe that corruption can overcome bureaucratic obstacles and rigid legal frameworks [2].…”
Section: The Impact Of Regional Corruption On Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Castillo (2018) studies corruption in state-owned enterprises; Saputra (2019) analyses the relationship between corruption and trade in developed and developing countries; Dheera-aumpon (2017) identifies peculiar features of corruption in the process of obtaining a bank loan; Nguedie (2018) focuses on the relationship between corruption and investment inflow and outflow. Corruption also affects innovative activities, where its effect is interpreted in different ways, however, noting that, eventually, it is a very negative phenomenon (Pirtea et al, 2019).…”
Section: Formation Of Input Statistical Base Of the Study Verificatimentioning
confidence: 99%